The effectiveness of psychiatric therapy against Malaysian cancer patients with depressive disorders : a systematic review - Amir Modarresi Chahardehi; Leila Mousavi; Shahizan Hasan (Penerbit Universiti Kebangsaan Malaysia, 2017)
The aim of this study is to compare depression in terms of treatment between psychotherapy and medical approach or to combine these approaches among cancer patients in Malaysia with respect to the cancer categories. It also studies the major prevalence of depressive disorder in the group together with the specialized clinical connection to the health outcomes. The annual incidence of cancer cases in Malaysia is 30,000 at late stage of the disease. We found 17 eligible researches out of 142 articles which most were under designed of cross-sectional or prospective study, and contained 2,523 cancer patients. This study was conducted on systematic electronic review using the databases such as Pub-Med, Scopus, ScienceDirect, Google Scholar, Wiley Online Library were carried out from the period of time between 2006 and 2015. For data collection purposes, the study goes through the Malaysian articles in English language, in which some of the considered factors were general management principles, cancer level among the depressed patients, the selection of the psychological therapies and the use of antidepressant medication. However, the evidences are still not enough to present an effective diagnostic method for the depressive disorders in cancer patients, and to find a successful antidepressant drug and/or an appropriate psychotherapy in this group of patients. Hence, many different approaches could be presented for psychotherapy. In conclusion, we found increased hazard rates for the cancer death among psychiatric patients compared to the control group without a registered mental illness.